Media and Onomastic Phraseology: A Study of Proper Names in Phraseological Units (Texas Journal of Multidisciplinary Studies, 2025)
This paper explores the role of media in the formation and dissemination of onomastic phraseological units across different linguistic systems. By analyzing English, Russian, and Uzbek media texts, the study identifies key trends in the use of proper names within phraseology. The research highlights how media discourse not only preserves traditional phraseological units but also actively contributes to the creation of new ones, reflecting sociopolitical and cultural contexts. The findings provide insights into the dynamic relationship between media, language, and cultural identity.